2008
DOI: 10.5194/adgeo-14-21-2008
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic anomalies observed at volcano Popocatepetl, Mexico

Abstract: Abstract.Results of the ULF geomagnetic monitoring of the volcano Popocatepetl (Mexico) and their analysis are summarized and presented for the period [2003][2004][2005][2006]. Our analysis reveals some anomalies which are considered to be of local volcanic origin: the EM background in the vicinity of the volcano was found to be significantly noisier than at other reference stations; sporadic strong noise-like geomagnetic activity was observed in the H-component; some geomagnetic pulsations were observed only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…A number of previous studies had reported a remarkable anomalous variation in the geomagnetic pulsations nearby several volcanoes (Johnston and Stacey, 1969;Johnston, 1997;Kotsarenko et al, 2005Kotsarenko et al, , 2008. Therefore, in the present study, the amplitude of the geomagnetic pulsation (Pc3 range) is examined to detect any characteristic signals that may be generated in relationship with the activity of the Mayon volcano.…”
Section: Data Analysis and Resultsmentioning
confidence: 90%
“…A number of previous studies had reported a remarkable anomalous variation in the geomagnetic pulsations nearby several volcanoes (Johnston and Stacey, 1969;Johnston, 1997;Kotsarenko et al, 2005Kotsarenko et al, , 2008. Therefore, in the present study, the amplitude of the geomagnetic pulsation (Pc3 range) is examined to detect any characteristic signals that may be generated in relationship with the activity of the Mayon volcano.…”
Section: Data Analysis and Resultsmentioning
confidence: 90%
“…Magnetic signals can also indicate periods of magma injection and gas pressure build-up; Negative magnetic anomalies during 1998-1999 were considered to be thermal caused by hot incoming magma while positive anomalies were related with dome cooling above the Curie point. Kotsarenko et al (2008), also noted thermally induced changes in the geomagnetic record. Sharp positive anomalies are stress related as was seen in the correlation with a tectonic regional earthquake and explosions (Martin-Del Pozzo, 2002c).…”
Section: Magneticsmentioning
confidence: 87%
“…Our earlier studies in the Popocatepetl Volcano area (2003)(2004)(2005)(2006) showed a variety of geomagnetic anomalies that were associated with volcano activity [Kotsarenko et al 2007] and also allowed us to propose the hypothesis of the existence of a second magmatic reservoir [Kotsarenko et al 2008]. The present study is devoted to various aspects of radon monotoring that was carried out in the first stage of our experimental investigations into the area of Popocatepetl Volcano (December 2007to December 2009.…”
Section: Special Issue: Earthquake Precursorsmentioning
confidence: 87%
“…The intensive radon release for Tlamacas Mountain encouraged us to revise our earlier discovered phenomena [Kotsarenko et al 2007[Kotsarenko et al , 2008: long-term noise was observed in the geomagnetic field measured at the Tlamacas station (Figure 6). To estimate the noise contribution, we compared the noise character for the Tlamacas station registered during a highly perturbed day with a referent signal contaminated by electric welding measured 200 m away from the welding source in Campus Juriquilla, Querétaro, during the construction of a new building.…”
Section: New View On the Volcano And Seismogenic Geomagnetic Emissionsmentioning
confidence: 99%